Method for preparing lithium iron phosphate material

Through microbial method and humic acid enrichment technology, the performance problems of lithium iron phosphate materials in low temperature environments and the low utilization rate of industrial iron waste liquids were solved, and high-performance lithium iron phosphate materials were prepared, which increased the material's plurality and low-temperature performance, and achieve efficient and green utilization of industrial iron-containing waste liquid.

CN119240645AActive Publication Date: 2025-01-03HEFEI GUOXUAN HIGH TECH POWER ENERGY

Patent Information

Application Number
CN202411368389.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-03
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

Lithium iron phosphate materials show poor discharge performance and rate performance in low temperature environments, and the utilization rate of industrial iron-containing waste liquid is low, resulting in waste of resources and environmental pollution.

Method used

The microbial method is used to convert Fe elements in industrial iron-containing waste liquid, and the carbon coating uniformity is improved through humic acid enrichment and two-step sintering technology to prepare high-performance lithium iron phosphate materials.

Benefits of technology

The high magnification and high and low temperature retention rate of lithium iron phosphate materials are achieved, the utilization efficiency of industrial iron-containing waste liquid is improved, and environmental pollution is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119240645A_ABST
    Figure CN119240645A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing a lithium iron phosphate material, and belongs to the technical field of lithium ion battery positive electrode materials. According to the method, the Fe element in the industrial iron-containing waste liquid is converted through a microbiological method, then enrichment is conducted through humic acid, the enrichment efficiency is high, and uniformity is good; the microbe-enriched iron complex is used as an iron source and a reducing agent, and the carbon coating uniformity is improved through two-step sintering, so that high magnification and high low-temperature retention rate are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion battery positive electrode materials, and specifically relates to a method for preparing lithium iron phosphate material. Background Art

[0002] Lithium iron phosphate cathode materials occupy an increasingly important market share in the field of electrode materials due to their economy and safety. However, lithium iron phosphate materials show poor discharge performance and rate performance in low temperature environments, which is mainly due to the poor conductivity of the material itself, the slow diffusion of lithium ions, and the changes in the electrolyte and SEI film at low temperatures. Therefore, improving the uniformity of carbon coating and improving the conductivity of lithium iron phosphate will have a positive effect on improving the low temperature and rate performance of the material, and can greatly expand the application scenarios of lithium iron phosphate materials at low temperatures.

[0003] With the continuous development of industrial production, the amount of industrial iron-containing waste liquid is also increasing year by year. According to relevant statistical data, the annual amount of scrap steel resources in my country has reached hundreds of millions of tons. Although industrial iron-containing waste liquid contains a large amount of valuable iron elements, the current utilization rate of industrial iron-containing waste liquid in my country is relatively low, resulting in waste of resources and environmental pollution. It is urgent to develop new iron-containing waste liquid recovery technology to achieve efficient and green recycling of iron resources. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a method for preparing high-performance lithium iron phosphate materials by a microbial method, aiming to simultaneously solve the technical problems of efficient utilization of industrial iron-containing waste liquid and poor uniformity of carbon coating of lithium iron phosphate materials and poor low-temperature performance.

[0005] The method for preparing high-performance lithium iron phosphate material by microbial method provided by the present invention comprises the following steps: 1) Add iron bacteria to industrial iron-containing wastewater to form wastewater A after reaction; 2) adding humic acid to the waste liquid A obtained in step 1), and filtering the precipitate after the reaction to obtain a complex precursor; 3) The complex precursor obtained in step 2) is mixed with a phosphorus source and a lithium source and then sintered in a protective atmosphere to obtain a lithium iron phosphate material.

[0006] The present invention converts the Fe element in industrial iron-containing waste liquid through a microbial method, and then enriches it through humic acid, with high enrichment efficiency and good uniformity; microorganisms enrich iron complexes as iron sources and reducing agents, and improve the uniformity of carbon coating through two-step sintering, thereby achieving high rate and high low-temperature retention rate.

[0007] In step 1) of the above method, the iron ion concentration in the industrial iron-containing waste liquid is 0.1-0.5 mol / L, and the pH is 2-7; The iron bacteria is Trichoderma spp.Leptothrix discophora )、Polysporin ( Crenothrix polyspora ferrooxidans ( Thiobacillus ferrooxidans ) one or more; The mass ratio of the iron bacteria (the live bacteria of the iron bacteria is 500-1000 cfu / g) to the industrial iron-containing waste liquid is: (0.001-0.005):1, the reaction time is 24-48 hours, and the reaction temperature is 5-30° C., so that Fe in the industrial iron-containing waste liquid is reduced to 0.1%. 2+ Completely converted to Fe 3+ , in order to improve the uniformity of subsequent humic acid complexation enrichment.

[0008] In step 2), the mass ratio of humic acid to waste liquid A is (0.01-0.05):1, and the reaction time is 10-36h.

[0009] In step 3), the molar ratio of lithium element in the lithium source, phosphorus element in the phosphorus source and iron element in the complex precursor is (1.01-1.10):1:(0.94-0.98).

[0010] In step 3), the sintering steps are: (1) heating to 400-600°C at a rate of 1-3°C / min and maintaining the temperature for 1-2 hours; (2) heating to 700-900°C at a rate of 1-3°C / min and maintaining the temperature for 3-12 hours.

[0011] The lithium iron phosphate material prepared by the above method also belongs to the protection scope of the present invention.

[0012] The application of the above lithium iron phosphate material in lithium ion batteries also falls within the protection scope of the present invention.

[0013] The present invention also provides a lithium ion battery, wherein the positive electrode of the lithium ion battery is prepared from the above-mentioned lithium iron phosphate material.

[0014] The beneficial effects of the present invention are as follows: (1) The Fe element in the iron-containing waste liquid is transformed and enriched by a microbial method, with high enrichment efficiency and good uniformity; (2) The iron complex enriched by microorganisms is used as an iron source, a reducing agent and a carbon source, and the uniformity of the carbon coating is improved by two-step sintering to achieve a high rate and a high and low temperature retention rate; (3) The present invention realizes the efficient, green and recyclable utilization of industrial iron-containing waste liquid, which is of great significance to resource conservation and environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 It is the SEM picture of the sample of Example 1; Figure 2 This is the SEM image of the sample in Comparative Example 1. DETAILED DESCRIPTION

[0016] The present invention is further described in detail below in conjunction with specific embodiments, and the examples provided are only for illustrating the present invention, rather than for limiting the scope of the present invention. The examples provided below can be used as a guide for further improvements by those of ordinary skill in the art, and do not constitute a limitation of the present invention in any way.

[0017] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.

[0018] The iron-containing waste liquid used in the present invention is the waste liquid generated after washing steel with hydrochloric acid.

[0019] Example 1 Add the following to the industrial iron-containing wastewater with an iron content of 0.1 mol / L and a pH of 5: Leptothrix Discophora ), wherein the live bacteria is 600 cfu / g, the mass ratio of the raw disc fiber hair fungus to the iron-containing waste liquid is 0.001:1, and the waste liquid A is formed after 24 hours of reaction at 25°C. Humic acid is added to the waste liquid A, wherein the mass ratio of humic acid to waste liquid A is 0.05:1, and the reaction time is 36 hours. Then, the precipitate is obtained by filtration, and lithium carbonate, phosphoric acid and the precipitate are uniformly mixed according to the (Li, P, Fe element molar ratio) of 1.02:1:0.96, and then sintered in a nitrogen atmosphere. The sintering steps are: (1) heating to 600°C at a rate of 3°C / min and keeping the temperature constant for 2 hours; (2) heating to 900°C at a rate of 1°C / min and keeping the temperature constant for 12 hours.

[0020] Example 2 Add Thiobacillus ferrooxidans ( Thiobacillus ferrooxidans ), wherein the live bacteria is 500 cfu / g, the mass ratio of Thiobacillus ferrooxidans to the iron-containing waste liquid is 0.003:1, and waste liquid A is formed after 24 hours of reaction at 25°C. Humic acid is added to waste liquid A, wherein the mass ratio of humic acid to waste liquid A is 0.02:1, and the reaction time is 36 hours. Then, the precipitate is obtained by filtration, and lithium carbonate, phosphoric acid and the precipitate are uniformly mixed according to the (Li, P, Fe element molar ratio) of 1.05:1:0.98, and then sintered in a nitrogen atmosphere. The sintering steps are: (1) heating to 500°C at a rate of 2°C / min and keeping the temperature constant for 2 hours; (2) heating to 900°C at a rate of 1°C / min and keeping the temperature constant for 8 hours.

[0021] Example 3 Add the following to the industrial iron-containing wastewater with an iron content of 0.1 mol / L and a pH of 3: Leptothrixdiscophora ), wherein the live bacteria is 760 cfu / g, the mass ratio of the raw disc fiber hair fungus to the iron-containing waste liquid is 0.005:1, and the waste liquid A is formed after 24 hours of reaction at 10°C. Humic acid is added to the waste liquid A, wherein the mass ratio of humic acid to waste liquid A is 0.05:1, and the reaction time is 24 hours. Then, the precipitate is obtained by filtration, and lithium carbonate, phosphoric acid and the precipitate are uniformly mixed according to the (Li, P, Fe element molar ratio) of 1.1:1:0.98, and then sintered in a nitrogen atmosphere. The sintering steps are: (1) heating to 500°C at a rate of 1°C / min and keeping the temperature constant for 1.5 hours; (2) heating to 800°C at a rate of 2°C / min and keeping the temperature constant for 8 hours.

[0022] Example 4 Add Polysporum quanfaciens ( Crenothrix polyspora ), wherein the live bacteria is 520 cfu / g, the mass ratio of polysporum fungus to iron-containing waste liquid is 0.005:1, and waste liquid A is formed after 36 hours of reaction at 10°C. Humic acid is added to waste liquid A, wherein the mass ratio of humic acid to waste liquid A is 0.05:1, and the reaction time is 10 hours. Then, the precipitate is obtained by filtration, and lithium carbonate, phosphoric acid and the precipitate are uniformly mixed according to the (Li, P, Fe element molar ratio) of 1.01:1:0.96, and then sintered in a nitrogen atmosphere. The sintering steps are: (1) heating to 500°C at a rate of 1°C / min and keeping the temperature constant for 1.5 hours; (2) heating to 800°C at a rate of 2°C / min and keeping the temperature constant for 8 hours.

[0023] Comparative Example 1 Add the following to the industrial iron-containing wastewater with an iron content of 0.1 mol / L and a pH of 5: Leptothrix discophora ), wherein the live bacteria is 600 cfu / g, the mass ratio of the raw disc fiber hair fungus to the iron-containing waste liquid is 0.001:1, and the waste liquid A is formed after reacting at 25°C for 24 hours. The waste liquid A is filtered to obtain a precipitate, and lithium carbonate, phosphoric acid and the precipitate are uniformly mixed according to the (Li, P, Fe element molar ratio) of 1.02:1:0.96, and then sintered in a nitrogen atmosphere. The sintering steps are as follows: (1) heating to 600°C at a rate of 3°C / min and keeping the temperature constant for 2 hours; (2) heating to 900°C at a rate of 1°C / min and keeping the temperature constant for 12 hours.

[0024] Comparative Example 2 Humic acid was added to industrial iron-containing waste liquid with an iron content of 0.1 mol / L and a pH of 5, wherein the mass ratio of humic acid to waste liquid was 0.05:1, and the reaction time was 36 hours. The precipitate was then filtered out, and lithium carbonate, phosphoric acid and the precipitate were uniformly mixed according to the molar ratio of lithium carbonate, phosphoric acid and the precipitate (Li, P, Fe elements) of 1.02:1:0.96, and then sintered in a nitrogen atmosphere. The sintering steps were as follows: (1) heating to 600°C at a rate of 3°C / min and keeping the temperature constant for 2 hours; (2) heating to 900°C at a rate of 1°C / min and keeping the temperature constant for 12 hours.

[0025] Comparative Example 3 Add the fibroblasts to the industrial iron-containing wastewater with an iron content of 0.1 mol / L and a pH of 8, wherein the fibroblasts ( Leptothrix discophora The mass ratio of 500 cfu / g) (live bacteria is 600 cfu / g) to iron-containing waste liquid is 0.001:1, and waste liquid A is formed after 24 hours of reaction at 25°C. Humic acid is added to waste liquid A, wherein the mass ratio of humic acid to waste liquid A is 0.05:1, and the reaction time is 36 hours. Then, the precipitate is obtained by filtration, and lithium carbonate, phosphoric acid and the precipitate are uniformly mixed according to the (Li, P, Fe element molar ratio) of 1.02:1:0.96, and sintered in a nitrogen atmosphere. The sintering steps are as follows: (1) heating to 600°C at a rate of 3°C / min and keeping the temperature constant for 2 hours; (2) heating to 900°C at a rate of 1°C / min and keeping the temperature constant for 12 hours.

[0026] Comparative Example 4 Add the following to the industrial iron-containing wastewater with an iron content of 0.1 mol / L and a pH of 5: Leptothrix discophora ) (live bacteria is 600 cfu / g), wherein the mass ratio of the raw disc fiber-hair fungus to the iron-containing waste liquid is 0.001:1, and waste liquid A is formed after 24 hours of reaction at 25°C. Humic acid is added to the waste liquid A, wherein the mass ratio of humic acid to waste liquid A is 0.5:1, and the reaction time is 2 hours. Then, the precipitate is obtained by filtration, and lithium carbonate, phosphoric acid and the precipitate are uniformly mixed according to the (Li, P, Fe element molar ratio) of 1.02:1:0.96, and then sintered in a nitrogen atmosphere. The sintering steps are: (1) heating to 600°C at a rate of 3°C / min and keeping the temperature constant for 2 hours; (2) heating to 900°C at a rate of 1°C / min and keeping the temperature constant for 12 hours.

[0027] Comparative Example 5 (Compared with Example 1, two-step sintering was not used) Add the following to the industrial iron-containing wastewater with an iron content of 0.1 mol / L and a pH of 5: Leptothrix Discophora), wherein the live bacteria is 600 cfu / g, and the mass ratio with the iron-containing waste liquid is 0.001:1, and waste liquid A is formed after 24 hours of reaction at 25°C. Humic acid is added to waste liquid A, wherein the mass ratio of humic acid to waste liquid A is 0.05:1, and the reaction time is 36 hours. Then, the precipitate is obtained by filtration, and lithium carbonate, phosphoric acid and the precipitate are uniformly mixed according to the (Li, P, Fe element molar ratio) of 1.02:1:0.96, and then sintered in a nitrogen atmosphere. The sintering steps are: heating to 900°C at a rate of 1°C / min, and keeping the temperature constant for 12 hours.

[0028] The lithium iron phosphate composite materials obtained in the above-mentioned experimental examples 1-4 and comparative examples 1-4 were subjected to physical, chemical and electrical performance tests. The electrical performance test method is as follows: a simulated battery is assembled using the materials obtained in the embodiments and comparative examples as the positive electrode, a battery-grade lithium sheet as the negative electrode material, and lithium hexafluorophosphate as the main component as the electrolyte, and relevant performance tests are performed. The initial charge and discharge capacity is tested at 0.2C, and the discharge capacity is tested at 1C and 2C in turn. Under the condition of 1C charge and discharge, the capacity retention rate is tested after 300 times.

[0029] The test results are shown in Table 1: Table 1 Comparison of electrical properties between comparative examples and examples

[0030] It can be seen from Table 1 that the method of the present invention has a positive significance for improving the rate performance and the low-temperature capacity retention rate. Among them, compared with Example 1, Comparative Example 1 did not add humic acid complexation, resulting in the iron element in the waste liquid not being enriched and unable to be uniformly contacted with the microbial carbon source, resulting in its sintering coating effect being unsatisfactory, and then the rate performance was reduced, and the low-temperature capacity retention rate was also low; Compared with Example 1, in Comparative Example 2, no iron bacteria were added, sufficient microbial reducing agents and carbon sources were not effectively introduced, and iron enrichment could not be performed, so the rate performance was reduced and the low-temperature capacity retention rate was also low; Compared with Example 1, the pH value of the industrial iron-containing waste liquid in Comparative Example 3 is higher, and the alkalinity affects the humic acid complexing effect, thereby reducing the rate performance and the low-temperature capacity retention rate; Compared with Example 1, the added amount of humic acid in Comparative Example 4 affects the complexing effect, thereby reducing the rate performance and the low-temperature capacity retention rate.

[0031] Compared with Example 1, Comparative Example 5 adopts two-step sintering to accurately control the phase formation and carbonization process of lithium iron phosphate, thereby improving the rate performance.

[0032] The present invention has been described in detail above. For those skilled in the art, without departing from the purpose and scope of the present invention, and without the need to carry out unnecessary experimental conditions, the present invention can be implemented in a wide range under equivalent parameters, concentrations and conditions. Although the present invention provides specific embodiments, it should be understood that the present invention can be further improved. In a word, according to the principles of the present invention, the application is intended to include any changes, uses or improvements to the present invention, including departure from the disclosed scope in the application, and changes made with conventional techniques known in the art.

Claims

1. A method for preparing lithium iron phosphate material, characterized in that: The method comprises the following steps: 1) Add iron bacteria to industrial iron-containing wastewater to form wastewater A after reaction; 2) adding humic acid to the waste liquid A obtained in step 1), and filtering the precipitate after the reaction to obtain a complex precursor; 3) The complex precursor obtained in step 2) is mixed with a phosphorus source and a lithium source and then sintered in a protective atmosphere to obtain a lithium iron phosphate material.

2. The method according to claim 1, characterized in that: In step 1), the iron ion concentration in the industrial iron-containing waste liquid is 0.1-0.5 mol / L, and the pH is 2-7.

3. The method according to claim 1, characterized in that The iron bacteria is Trichoderma spp. Leptothrix Discophora )、Polysporin ( Crenothrix polyspora ferrooxidans ( Thiobacillus ferrooxidans ) 4. The method according to claim 1, characterized in that: The viable bacteria of the iron bacteria are 500-1000 cfu / g; The mass ratio of the iron bacteria to the industrial iron-containing waste liquid is: (0.001-0.005):1, the reaction time is 24-48h, and the reaction temperature is 5-30°C.

5. The method according to claim 1, characterized in that In step 2), the mass ratio of humic acid to waste liquid A is (0.01-0.05):1, and the reaction time is 10-36h.

6. The method according to claim 1, characterized in that In step 3), the molar ratio of lithium element in the lithium source, phosphorus element in the phosphorus source and iron element in the complex precursor is (1.01-1.10):1:(0.94-0.98).

7. The method according to claim 1, characterized in that In step 3), the sintering steps are: (1) heating to 400-600°C at a rate of 1-3°C / min and maintaining the temperature for 1-2 hours; (2) heating to 700-900°C at a rate of 1-3°C / min and maintaining the temperature for 3-12 hours.

8. Lithium iron phosphate material prepared by the method according to any one of claims 1 to 7.

9. Use of the lithium iron phosphate material according to claim 8 in lithium ion batteries.

10. A lithium ion battery, characterized in that: The positive electrode of the lithium-ion battery is prepared from the lithium iron phosphate material according to claim 8.

Citation Information

Patent Citations

  • Complex acidophilic microbial agent as well as preparation method and application thereof in treating waste copper-clad plate flotation residue

    CN105132319A

  • Method for recycling metal in lithium ion battery through inorganic acid leaching-bioleaching collaboration

    CN108285980A

  • Method for preparing lithium iron phosphate positive electrode material by taking pickling iron oxide red as raw material

    CN110021747A

  • Method for selectively leaching and recycling lithium in black powder of waste lithium iron phosphate power battery by using acidithiobacillus ferrooxidans

    CN114959304A

  • The method of treatment of iron-containing waterworks sludge and a mixture prepared by this method

    EP1985590A1

Cited By

  • Regeneration method for specifically repaired waste lithium iron phosphate battery

    CN121565976A